Pengaruh Partisipasi Siswa Terhadap Prestasi Akademik Siswa UPTD SD Negeri Kemayoran 1 Bangkalan - Salsabiela, Rahma Julia; Mardiyana, Isna Ida; Susetiawati, Yuhanisah Prisma (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to analyze the influence of student participation on academic achievement at SDN Kemayoran 1 Bangkalan. The research method used is associative quantitative, involving 10 students as samples. Student participation data were obtained through a questionnaire that measures the level of student involvement in learning activities, with a value scale from 1 (very low) to 5. (very high). Academic achievement is measured using report card grades or semester exam results in mathematics subjects. Data analysis was conducted using the Pearson correlation test and simple linear regression. The research results show a significant positive relationship between student participation and academic achievement, with a Pearson correlation coefficient of 0.82 and the influence of student participation on academic achievement being 2.5 points per unit increase in participation score. These findings indicate that more active student participation is directly related to the improvement of their academic performance. Therefore, it is important for educators to encourage student participation in learning to improve the quality of education and students' academic outcomes